Peran self-esteem terhadap ketangguhan mental mahasiswa - Yulita Anggelia; Ira Adelina; Priska Analya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Pursuing higher education is a challenging journey that requires students to be active, independent, and capable of critical and creative thinking. This study aims to examine the influence of self-esteem on students’ mental toughness. A quantitative correlational design was employed, involving 73 university students in Bandung, Indonesia. Data were analyzed using simple linear regression. The results showed that self-esteem has a significant positive relationship with mental toughness (r = 0.699, p < .001), indicating a strong correlation. Furthermore, self-esteem significantly predicts mental toughness, accounting for 48.9% of the variance (R² = .489). These findings suggest that higher levels of self-esteem are associated with higher mental toughness. This study highlights the importance of self-esteem as a key psychological factor in enhancing students’ resilience in academic contexts